The "Special" crystal-Stellate System in Drosophila melanogaster Reveals Mechanisms Underlying piRNA Pathway-Mediated Canalization. - Bozzetti, M.P.; Fanti, L.; Di Tommaso, S.; Piacentini, L.; Berloco, M.; Tritto, P.; Specchia, V. (Genetics research international, 2012)
The Stellate-made crystals formation in spermatocytes is the phenotypic manifestation of a disrupted crystal-Stellate interaction in testes of Drosophila melanogaster. Stellate silencing is achieved by the piRNA pathway, but many features still remain unknown. Here we outline the important role of the crystal-Stellate modifiers. These have shed light on the piRNA pathways that defend genome integrity against transposons and other repetitive elements in the gonads. In particular, we illustrate the finding that HSP90 participates in the molecular pathways of piRNA production. This observation has relevance for the mechanisms underlying the evolutionary canalization process.